2014
DOI: 10.1016/j.drugalcdep.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of marijuana use change and cessation among adolescents

Abstract: Background With marijuana use increasing among American adolescents, better understanding the factors associated with decreasing use and quitting can help inform cessation efforts. This study evaluates a range of neighborhood, family, peer network, and individual factors as predictors of marijuana use change and non-use over one year, and cessation over six years. Methods Data come from adolescents in Waves I and II of the National Longitudinal Study of Adolescent Health (N=458, one-year sample), or Waves I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Extensive research has shown that peer context is a very robust predictor of cannabis use (Pollard, Tucker, de la Haye, Green, & Kennedy, 2014). For example, a recent study demonstrated that when actual friends’ cannabis use increased, personal cannabis increased (Deutsch, Chernyavskiy, Steinley, & Slutske, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that peer context is a very robust predictor of cannabis use (Pollard, Tucker, de la Haye, Green, & Kennedy, 2014). For example, a recent study demonstrated that when actual friends’ cannabis use increased, personal cannabis increased (Deutsch, Chernyavskiy, Steinley, & Slutske, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 However in longitudinal studies of adolescents, including those accounting for cannabis use disorders, non-Hispanic black adolescents and young adults and those identifying with two or more racial categories appear to be at greater risk. 6,7 Furthermore, as local data may differ significantly from findings in national data sets, closer examination of sociodemographic associations with marijuana use in a diverse population of young adults may suggest unique targets for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Research supports the clinical effectiveness of targeting adolescent peer network characteristics with brief interventions (Chung et al, 2015). Peer context is a very robust predictor of cannabis use (Pollard et al, 2014); thus, integrating peer networks into cannabis use interventions is warranted.…”
mentioning
confidence: 99%